INNOVATIVE METHODS OF FINANCING IN AGRICULTURE: CROWDFUNDING - Alikulov Mekhmonali Salakhiddin ugli (American Journals, 2025)
The article studies the opinions of leading world scientists on innovative methods of financing agriculture: crowdfunding, discusses in detail the main features and types of crowdfunding platforms and mechanisms in the agricultural sector, analyzes platforms designed to support agricultural projects around the world, conducts a SWOT analysis of crowdfunding platforms designed to support agricultural projects, and develops substantiated conclusions and proposals for the introduction of crowdfunding in the farming sector in Uzbekistan.
Keywords: Agriculture, innovative financing, crowdfunding, crowdfunding in agriculture, agro finance, online investments, crowdfunding, farming projects, electronic platform, social fundraising.